A study on the different aspects of set design on the stage play presentation "Buwan at Baril" - Crisostomo, Nancy R.; Florendo, Raquel Baltazar (1989.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Set designers -- Philippines; Theaters -- Stage-setting and scenery